INCREASING THE STUDENTS’ ABILITY IN WRITING RECOUNT TEXT THROUGH LANGUAGE EXPERIENCE APPROACH AT THE EIGHTH GRADE OF SMP NEGERI 5 DHARMA CARAKA TELUKDALAM - SENADAMAN WAU (Jurnal Education and Development, 2017)
The objective of the research is to increase the students’ ability in writing recount text through Language Experience Approach (LEA) at the eighth grade of SMP Negeri 5 Dharma Caraka Telukdalam. The research design is classroom action research (Kemmis et al 2014). This action research is conducted into two cycles, and each cycle consists of two meetings. The instruments of data collection are observation papers and written test. The qualitative data are analyzed by using Miles, Huberman, & Saldana’s theory (2014), and quantitative data are analyzed by using Gay et al (2000). The finding is Language Experience Approach increases the students’ ability in writing recount text at the eighth grade of SMP Negeri 5 Dharma Caraka Telukdalam. The increasing is supported by the students’ average score that in cycle I is 56.75, and in cycle II is 85.45. It is suggested to English teachers to use LEA as the approach of teaching and learning of writing.